The Effect Of Offensive Tactical Exercises On Endurance, Ability, And Scoring Accuracy Among Players Of The University Of Al-Kut Futsal Team (Journal of the College of Basic Education, 2026)
The importance of the research emerged in developing offensive tactical exercises, to develop the ability to endure and the accuracy of scoring among the players of the University of Al-kut Futsal team, the purpose of which is to continue playing, which requires a distinctive strength in speed (ability) and to endure this ability for a relatively long period of time (endurance of strength distinguished by speed) or (endurance of ability) that performs an important function in repeating the implementation of the skillful and tactical performance with high efficiency during training and matches. The research aimed to prepare offensive tactical exercises for the players of the University of Al-kut futsal team. And to identify the effect of offensive tactical exercises on endurance capacity and scoring accuracy among the players of the University of Al-kut futsal team. As for the research methodology, the researchers followed the experimental approach. The research community and its sample were the players of the University of Al-kut Futsal team for the academic year 2024-2025, numbering (16) players. The research sample was chosen intentionally, which was (14) players after excluding goalkeepers due to the legal specificity of their game. They were divided randomly equally into two groups, a control and an experimental group. The research sample constituted (87.5%) of the research community. After the researchers conducted the pre-tests and applied the planning exercises and conducted the post-tests, the results were processed, presented and discussed. Based on these results, the researchers reached the most important conclusions, which are: Offensive tactical exercises raised the players' physical level, especially their endurance. This was because the exercises were characterized by continuity and standardization in their application, in addition to being characterized by changing direction, rapid rotation, and exchanging positions between players. This is what causes the players to reach a stage of fatigue during performance